It doesn't cost anything just to ask, does it? The ethics of questionnaire-based research. Issue 1 (1st February 2002) - Evans, M; Robling, M; Maggs Rapport, F; Houston, H; Kinnersley, P; Wilkinson, C
Abstract : Patient-based outcome measures are increasingly important in health care evaluations, often through the use of paper-based questionnaires. The likely impact of questionnaires upon patients is not often considered and therefore, the balance of benefit and harm not fully explored. Harms that might accrue for research staff are even less frequently considered. This paper describes the use of postal questionnaires within a study of breast disease management in primary care. Questionnaire responses are used to describe the nature of discomfort or harms that may occur in such studies. Ethical issues raised by the harms are discussed in relation to the benefits of the study. Practical suggestions for reducing harm to patients are proposed. A secondary consideration, discomfort to the researcher, is also identified and suggestions made to reduce its effect. Finally, the role of research questionnaires as a study intervention is discussed.